Biodiversity footprint of food products and perceptions of biodiversity footprint information : Case S Group - Hynönen, Laura (2024)
Agriculture is one of the major causes of biodiversity loss, contributing to land use, climate change, and pollution. At the same time, food system is highly dependent on biodiversity and ecosystems. There is a need for systemic shift towards more sustainable food industry and dietary patterns to mitigate global biodiversity loss. Retail companies can play an important role in the efforts to develop food supply chains and consumption patterns more sustainable. The shift from status quo requires information about the adverse biodiversity impact of human activities and consumption as well as leadership towards environmental sustainability. In this study, production country specific terrestrial biodiversity footprints for ten protein-rich food products were assessed per three functional units: retail weight, protein content, and energy content. In addition, the purpose of this study was to gain business perception of utilizing such biodiversity footprint information. The results showed that different sources of proteins and production countries have substantially different biodiversity footprints. Plant originated proteins had significantly lower biodiversity footprint than animal originated proteins. From the business perspective, biodiversity footprint information was considered useful. The results revealed benefits, challenges, and needs related to applying biodiversity footprint in business context.